Blood and immunity - Cyber Ed Inc (Chico, Calif. : Cyber Ed, 1997)
This interctive educational program includes : presentation, jump presentation, interctive lessons, pre and post testing, online interctive glossary.
Systems requirements : IBM-Compatible PC, 4 MB available RAM memory (8MB or higher), hard disk space 256k,Windows 3.1, 95 or higher, S-VGA graphics, CD-ROM drive (2x speed preferred)
Keywords: Blood; Immune system